2013
DOI: 10.1039/c3cc42981d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical unfolding of long human telomeric RNA (TERRA)

Abstract: We report the first single molecule investigation of TERRA molecules.By using optical-tweezers and other biophysical techniques, we have found that long RNA constructions of up to 25 GGGUUA repeats form higher order structures comprised of single parallel G-quadruplex blocks, which unfold at lower forces than their DNA counterparts.Telomeres are nucleoprotein structures that protect chromosome ends from being recognized as DNA breaks.1 Mammalian telomere DNA consists of long tandem arrays of double-stranded TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
(67 reference statements)
1
26
2
Order By: Relevance
“…It is interesting that the partially folded structure has a rupture force comparable to that of RNA GQ (Figure 3), which suggests that the partially folded structure is more rigid but also more fragile than the fully folded GQ. During the submission of this paper, it was reported that rupture force for a TERRA construct that contains five telomeric repeats is lower than what we have observed here 32. It is possible that the additional telomeric repeat may reduce the mechanical stability of the RNA quadruplex.…”
contrasting
confidence: 48%
“…It is interesting that the partially folded structure has a rupture force comparable to that of RNA GQ (Figure 3), which suggests that the partially folded structure is more rigid but also more fragile than the fully folded GQ. During the submission of this paper, it was reported that rupture force for a TERRA construct that contains five telomeric repeats is lower than what we have observed here 32. It is possible that the additional telomeric repeat may reduce the mechanical stability of the RNA quadruplex.…”
contrasting
confidence: 48%
“…Optical tweezers represent a unique approach to investigate the mechanical stability of folded nucleic acid structures at the single-molecule level1438394041. This technique has been used to demonstrate the formation of G-triplex structures formed by human telomeric sequences containing three GGG repeats under dilute conditions and in the presence of Na + ion14.…”
Section: Resultsmentioning
confidence: 99%
“…The rupture-force histogram for the TERRA GQ without ligands shows more than one population (Figure 4 A ), representing multiple conformations in the same TERRA sequence as reported previously. [ 24 , 28 ] When the TERRA construct was incubated with 5 μ m cPDS, we observed an increase in the rupture forces (from 23/36 pN to 25/40 pN), thus suggesting that the binding of cPDS increases the mechanical stability of the TERRA GQ (Figure 4 B ). A similar increment in mechanical stability was observed for TERRA-G4 with 50 n m BG4 (Figure 4 C ).…”
mentioning
confidence: 91%